1982
DOI: 10.1002/j.1875-9114.1982.tb03187.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Moxalactam: Antimicrobial Activity, Pharmacokinetics, Adverse Reactions, and Clinical Efficacy

Abstract: Although moxalactam is not, technically speaking, a cephalosporin it is chemically and microbiologically so closely related to those compounds that it can be viewed as a member of the cephalosporin family. Moxalactam has a spectrum of activity that includes both gram positive and gram negative bacteria. Its gram positive activity is less than earlier cephalosporins, but its activity against the Enterobacteriaceae is similar to that of the aminoglycoside family of antibiotics in most comparative studies. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…However, clinical studies have identified problems when patients with some Pseudomonas aeruginosa infections are treated with moxalactam. In addition, the activity of moxalactam against many gram-positive bacteria, including penicillinase-producing Staphylococcus aureus strains, is less than the activity of the first-generation cephalosporins (6). Imipenem, a new beta-lactam antibiotic, has the broad spectrum required to treat sepsis that is presumed * Corresponding author.…”
mentioning
confidence: 99%
“…However, clinical studies have identified problems when patients with some Pseudomonas aeruginosa infections are treated with moxalactam. In addition, the activity of moxalactam against many gram-positive bacteria, including penicillinase-producing Staphylococcus aureus strains, is less than the activity of the first-generation cephalosporins (6). Imipenem, a new beta-lactam antibiotic, has the broad spectrum required to treat sepsis that is presumed * Corresponding author.…”
mentioning
confidence: 99%
“…Azlocillin, cefazolin, imipenem, moxalactam, phenoxymethylpenicillin/penicillin V, and piperacillin are mostly eliminated by glomerular filtration, with some of them also eliminated by active secretion dependent on organic anion transporter (OAT) 1 and 3 or the multidrug resistance protein 4 (MPR4). 68,81,89,114,116–118…”
Section: Resultsmentioning
confidence: 99%
“…Azlocillin, cefazolin, imipenem, moxalactam, phenoxymethylpenicillin/penicillin V, and piperacillin are mostly eliminated by glomerular filtration, with some of them also eliminated by active secretion dependent on organic anion transporter (OAT) 1 and 3 or the multidrug resistance protein 4 (MPR4). 68,81,89,114,[116][117][118] Other antibacterial drugs also undergo biliary elimination without the renal route, such as ceftriaxone [renal OAT 1/ 3 and hepatic organic-anion-transporting polypeptides (OATP) 1B3] and cefotaxime (renal OAT 3 and MRP4 and hepatic OATP1B3) or just biliary elimination such as cefoperazone (OATP1B3). 68,114,119 Therefore, this review highlights the importance of quantifying the effect of pregnancy on the activity of drug transporters because glomerular filtration alterations are already well known.…”
Section: Antibacterial Drugsmentioning
confidence: 99%
“…The MIC 90 of Staphylococcus aureus ( S. aureus ) strains ranged from 4 to 16 µg/ml. Latamoxef has similar activity against penicillin-resistant and -sensitive strains of S. aureus , but methicillin-resistant S. aureus is resistant to latamoxef (MIC 90 > 64 µg/ml) ( 15 18 ). The MIC 90 of latamoxef for Streptococcus pneumoniae ( S. pneumoniae ) and Streptococcus pyogenes ( S. pyogenes ) varies from 1 to 3 μg/ml ( 18 ).…”
Section: Latamoxef Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Hypersensitivity may occur in approximately 2%–3% of patients treated with latamoxef and consist of symptoms including rashes, occasional fever, and eosinophilia ( 1 , 18 , 47 ). This was the most common reason for stopping treatment ( 1 ).…”
Section: Latamoxef Pharmaceutical Care Based On Adverse Drug Reactionsmentioning
confidence: 99%